THE REALIZATION OF POLITENESS STRATEGIES BY INDONESIAN WOMEN AS NON-NATIVE SPEAKERS OF ENGLISH WHEN EXPRESSING REFUSALS - Mirsah Winda, - (2012)
The main purpose of the present study is to investigate the realization of politeness strategies of refusals by Indonesian women as non-native speakers of English. Data have been collected through questionnaires in the form of discourse completion test (DCT) and interview, involving 20 women who are currently living in an English speaking country, in this case, United State of America. Brown and Levinson's (1987) politeness strategies have been used in the process of analyzing the obtained data. The study reveals that Indonesian women as non-native speakers of English have realized all four types of politeness strategies, with negative politeness strategy being the most frequent. Respondents took social distance, relative power, and ranking of imposition into account in performing politeness strategies, but none of these social variables has dominant influence towards the realization of politeness strategies in refusal. The result shows that negative politeness strategy was used constantly in the three social variables. The finding then says, with the three social variables involved, the respondents have performed negative politeness with question/hedge, be pessimistic and apologize as the characteristics. The strategy used by the respondents is the same with the Americans' when expressing refusals. It indicates that the respondents tend to be native-like. This study can be used as an input for those who are interested in conducting a research of intercultural communication, sociolinguistics, and pragmatics.